The causation of hydrogen embrittlement of duplex stainless steel: Phase instability of the austenite phase and ductile-to-brittle transition of the ferrite phase – Synergy between experiments and modelling. (June 2023) - Örnek, Cem; Mansoor, Mubashir; Larsson, Alfred; Zhang, Fan; Harlow, Gary S.; Kroll, Robin; Carlà, Francesco; Hussain, Hadeel; Derin, Bora; Kivisäkk, Ulf; Engelberg, Dirk L.; Lundgren, Edvin; et al.
Abstract: Various mechanisms have been proposed for hydrogen embrittlement of duplex stainless steel, but the causation of hydrogen-induced material degradation has remained unclear. This work shows that phase instability (decomposition) of the austenite phase and ductile-to-brittle transition of the ferrite phase precedes hydrogen embrittlement. In-situ diffraction measurements revealed that Ni-rich sites of the austenite phase decompose into metastable hydrides. Hydride formation is possible by increasing the hydrogen chemical potential during electrochemical charging and low defect formation energy of hydrogen interstitials. Our findings demonstrate that hydrogen embrittlement can only be understood if measured in situ and in real-time during the embrittlement process. Graphical Abstract: ga1 Highlights: Hydrogen embrittlement of stainless steel is due to phase separation reactions. Nickel-rich hydrides can be formed during hydrogen absorption. Hydride are formed due to increasing the hydrogen chemical potential during H uptake. Most hydrogen-induced lattice changes occur in the austenite phase. Understanding hydrogen embrittlement requires in-situ and real-time testing.